A Result and Discussion of the Dynamic Assessment Approach in Language Teaching: A Literature Review Study - M Arinal Rahman; Nurhafisah Nurhafisah; Shahid Rasool; Izzah Supeni (PANYONARA: Journal of English Education, 2022)
Dynamic assessment is conceptually based on the sociocultural theory of Lev Vygotsky in the Zone Proximal Development. This paper aimed to discuss dynamic assessment in assessing students` reading comprehension. The limitation of this article will only discuss the definition of dynamic assessment, the historical framework of dynamic assessment, teacher roles in dynamic assessment, dynamic assessment in a foreign language, dynamic assessment of writing, dynamic assessment of reading comprehension, and the advantages and disadvantages of dynamic assessment. Based on literature studies, the dynamic assessment approach is effective in English teaching. It can conclude that this approach can be adopted and developed by English teachers to encourage students` motivation and participation in learning English.